Pengembangan Sistem Manajemen Proyek Perangkat Lunak (Studi Kasus: CV. Karya Studio Teknologi Digital) - Robi Hidayat; Achmad Arwan; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Software project management is very important to the success of a software project. KS is a company that specializes in developing software projects. The main problem that happens with Karya Studio concerning software project management is that project managers often have difficulty monitoring the progress of tasks that are carried out by programmers. The cause of this problem is the lack of a system that records the progress of tasks that the programmer is doing. All progress reports from the programmers are stacked in one report in the group chat. Another issue is that the client cannot directly monitor the progress of the project and therefore cannot provide early feedback if there is a work error in the project. A software project management system was built to solve these problems. It is expected that with this system, a software project can be managed in one platform so that coordination between Karya Studio team members and clients can be carried out in a more structured and systematic manner. This system is developed using a waterfall model software development life cycle. The phases of this study include literature review, requirements engineering, system design, implementation and testing. This system is developed on a web platform using the single page application (SPA) concept. This system has been tested using unit tests, integration tests, validation tests, and compatibility tests.